Examining the Influence of e-Health Literacy on Healthcare Workers’ Acceptance of Electronic Medical Records: An Insight Into System Transition - Noeryosan, Ilham; Arini, Merita; Binti Wan Mamat, Wan Hasliza (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
Following the aftermath of COVID-19, needs of digitalized medical data system has increased worldwide. As stated by Indonesia’s Ministry of Health, electronic medical records (EMRs) usage are being mandated initially by December 2023. However, in some healthcare facilities, this transition are being halted by inadequate digital literacy. This research aimed to understand the impact of e-Health Literacy of healthcare personnel on technology acceptance and their intention to use EMRs. The cross-sectional study was conducted in March 2024 following six months of EMR implementation in Dr. Soetarto Army Hospital, using a valid and reliable questionnaire consisting of 51 items originating from the Unified Theory of Acceptance and Use of Technology (UTAUT) and e-Health Literacy Questionnaire (eHLQ) that was modified into 46 items. The data was collected from 114 healthcare personnel who act as both caregiver and medical data documenter (total sampling). The result was then analyzed using Smart-PLS. There is an increased intention of EMR usage when e-health literacy moderated user's technology acceptance (p=0.006), while by itself, technology acceptance doesn't have a meaningful impact towards intention to use EMR (p=0.391). Increased e-Health Literacy has also proven to be correlated with increased intention of EMR use (p<0.001). Increasing user’s e-health literacy is essential to become a pivotal factor in increasing EMR adoption in healthcare personnel workflow. This study suggests integrating targeted e-health literacy programs into professional development to improve EMR usage and healthcare efficiency, with future studies exploring long-term.